MISCONCEPTIONS ON REDOX REACTIONS USING THE FOUR TIER TEST (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2023)
The purpose of this research is to show the percentage of misconceptions experienced by students in class X MAN 3 Hulu Sungai Selatan by doing a four-tier test (four-level test) for each subconcept. The type of research used is descriptive statistics with a quantitative approach. The population of this study were students of class X MAN 3 Hulu Sungai Selatan with samples of class X MIA 1 and 2 totaling 63 people. The sampling technique used is purposive sampling. The data collection technique used a diagnostic test in the form of a four-tier test. The results showed that there was a misconception about the redox reaction material with an average of 33.45% which met the moderate criteria. Misconceptions of subconcepts Redox reactions are based on the gain and release of oxygen (16.67%), based on the gain and loss of electrons (39.68%), increase and decrease in oxidation number (38.10%), Oxidation number (12.70%), Oxidation-reduction reactions (44.44%), oxidizing agents and reducing agents (30.16%), and application of redox reactions (52.38%). The biggest misconception is in the sub-concept of applying redox reactions.